Pemanfaatan Limbah Kulit Kakao (Theobroma Cacao. L) sebagai Pakan Ternak - Yulius Nura Ade; Julianus Jeksen; Almaria Heliana (Universitas Muhammadiyah Manado, 2023)
Cocoa pod shell waste is the largest waste generated from cocoa plants that will cause problems for the environment if not processed properly. Further processing is needed in order to reduce pollution problems. Fresh cocoa fruit shells have a good nutrient content of 88% dry matter, 11.71% crude protein, 20.79% crude fiber, 11.80% fat and 34.90% extractable material without nitrogen (BETN). However, cocoa pods have a disadvantage when given as sole feed, due to the presence of theobromine in cocoa pods. This substance can inhibit the growth of rumen microbes. It is better to do fermentation first to increase digestibility and livestock liking of the feed. Protein content in cocoa pods can play a role in helping the growth or formation of body cells, especially in young cows and support production needs in adult cows. The crude fiber contained in cocoa pods is a complex carbohydrate that is needed by livestock in launching the digestive process. Meanwhile, fat contained in cocoa pods can play an important role for the growth and development of livestock and become a reserve source of energy. Fat serves as a carrier of vitamins in the body, especially vitamins A, D, E, and K because these vitamins are the type of vitamins that can dissolve in fat.